THE SCOPING REVIEW OF CHINESE AND WESTERN MEDICINE TREATMENT OF DIABETIC FOOT IN ASIA - Xinyan, Wang; Yinuo, Wang; Hanyi, Yu; Aslam, Muhammad Shahzad (Universal Journal of Pharmaceutical Research, 2020)
Diabetic foot is a common and serious chronic complication of diabetes due to the simultaneous occurrence of diabetic peripheral neuropathy and vascular lesion. Among all complications, foot ulcers in diabetic ulcers account for the first place among the reasons for hospitalization and treatment of diabetic patients. 15% of diabetic patients may have foot diseases, and 85% of patients may have foot ulcers as the cause of amputation. Diabetic foot seriously affects the quality of life of patients. Although there are many methods to treat diabetic foot, the therapeutic effect of diabetic foot is not ideal in general. The main purpose of this scoping review was analyzing the existing loopholes of researches on diabetic foot in Asia. Used Pub Med, CNKI, Wangfang data, CQVIP to search and select 5 traditional Chinese medicine literatures and 5 western medicine literature, through the comparison of various conditions between literature to analyze the lack of research. Ten pieces of literature were retained through 183 records and included 9 drugs or decoction, they were adipose-derived stem cell–hydrogel complex, hyperbaric oxygen therapy, Xenogeneic (porcine) a cellular dermal matrix, alprostadil, salvia miltiorrhiza polyphenols for injection and collagen sponge, Taohong Siwu Decoction, Simiao Yong an Decoction, Jiawei Simiao Yong an Decoction, Huangqi Guizhi Wuwu Tang, and Wuwei Xiaodu Drink. The obvious problems found by this scoping review were the quantity and quality deficiency of the research in the diabetic foot in Asia. Scoping review is an effective method of evidence identification and synthesis, which can provide a basis for the further development of a certain field. In the further study of the diabetic foot, more attention should be paid to the verification of experimental data as well as the feasibility of the researches on oral drugs. Peer Review History: Received 5 February 2020; Revised 11 March; Accepted 25 April; Available online 15 May 2020 Academic Editor: Dr. Ali Abdullah Al-yahawi , Al-Razi university, Department of Pharmacy, Yemen, alyahawipharm@yahoo.com Reviewer(s) detail: Dr. Sabah Hussien El-Ghaiesh , Tanta University, Egypt, s.ghaiesh@gmail.com Dr. Mohamed Derbali , Faculty of Pharmacy, Monastir, Tunisia, mohamed.edderbali@gmail.com